Dynamics of lipid profile and circadian pressure rhythms in patients with obesity and arterial hypertension, treated with orlistat and its combination with ACE inhibitors - A. G. Avtandilov; A. S. Ametov; A. K. Ausheva; A. K. Bolotseva (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To assess effects of orlistat and its combimation with enalapril on main cardiovascular risk parameters in young patients with obesity and arterial hypertension. Material and methods. In 60 young patient with obesity, dyslipidemia and arterial hypertension (AH), anthropometry, lipid profile assessment, 24-blood pressure monitoring (BPM) were performed. Group I (n=30) received orlistat, Group 2 (n=30) received orlistat (120 mg 3 times per day) and enalapril (10-20 mg/d). Results. After 3 months of therapy, significant decrease in body weight and body mass index (MBI), as well as lipid profile normalization, was observed in both groups. At the same time, in Group 2 total cholesterol, triglycerides and atherogenity index decrease was more pronounced. According to 24-hour BPM results, systolic and diastolic blood pressure (BP) levels significantly declined both in day- and nighttime, especially in Group 2. Conclusion. Orlistat treatment, combined with low-caloric diet, decreased bdy weight and normalized BP level. At the same time, a combination of orlistat and enalapril was associated with more pronounced beneficial dynamics of plasma lipid profile, and significant BP decline.